Misuse of Ambulances for Nonmedical Purposes and Legal Consequences: Penyalahgunaan Ambulans untuk Tujuan Nonmedis dan Konsekuensi Hukumnya - Putri Aldora Muaini; Mochammad Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Ambulances are priority emergency vehicles intended exclusively for medical rescue and patient transport, supported by special traffic privileges and regulated standards within public health systems. Specific Background Recent practices in Indonesia reveal ambulances being deployed for nonmedical activities, including personal transportation, logistics delivery, criminal acts, and political interests, raising concerns about public safety, service disruption, and ethical compliance. Knowledge Gap Existing studies have not comprehensively examined the forms of nonmedical use alongside the legal responses and sanctions across multiple legal domains within a single sociolegal framework. Aims This study analyzes the types of ambulance misuse for nonmedical purposes, the mechanisms of law enforcement applied, and the legal implications for perpetrators. Results Using a sociolegal empirical approach, the findings show that misuse occurs in criminal, civil, employment, and administrative contexts; enforcement actions vary according to the actor and consequences; and sanctions range from imprisonment and compensation to termination of employment and disciplinary measures, with preventive and repressive efforts sometimes complemented by restorative justice. Novelty The study offers an integrated normative-empirical analysis that links real-world practices with statutory provisions, highlighting gaps in supervision and accountability concerning emergency vehicle use. Implications Strong, coordinated enforcement and oversight are necessary to preserve the humanitarian function of ambulances, maintain public trust in emergency services, and ensure that priority road rights remain reserved for genuine medical emergencies. Highlights: Nonmedical use appears across criminal, civil, labor, and administrative violations. Penalties differ according to perpetrator role and severity of consequences. Coordinated oversight is required to safeguard emergency service integrity. Keywords:Ambulance Misuse; Emergency Vehicle Regulation; Law Enforcement; Legal Sanctions; Sociolegal Study